Digital Communication In Customer Satisfaction: A Case Study On The Use Of Satisfaction Surveys - Handayanti, Asih; Darmawan, Ferry (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The use of digital surveys is becoming increasingly important in collecting customer satisfaction data, especially in the competitive garment accessories industry. However, the limited representation of respondents in digital surveys remains a challenge. This study aims to explore the factors that influence customer satisfaction, focusing on product quality, service speed, and feedback systems. A qualitative approach with a case study method is applied to understand customer experiences in depth. Data were collected through an online survey focusing on key aspects of customer satisfaction and analyzed descriptively. The findings show that product quality is a key factor in customer satisfaction, while service speed and a responsive feedback system become more important for new customers. Although digital surveys are effective in capturing customer perceptions, bias can occur due to the limited representation of customers less familiar with digital technology. These results align with findings in other industries, which show the importance of service quality and responsive interactions in building customer satisfaction. However, a multi-channel approach is recommended to improve respondent representation in digital surveys. This research provides insights into the factors that affect customer satisfaction in a digital context and recommends a multi-channel survey strategy to improve the validity and representativeness of the results.